Caracterização do isolamento acústico de polímeros reciclados adicionados de fibras de bambu utilizando análise do coeficiente de absorção sonora em tubos de impedância - Lima, Abner Guilherme Teixeira (2016)
The use of vegetal fibers added to polymers has been considerably increasing over the last few years, both for economic reasons as for environmental concerns. As an example of the latter, we have the new European directive (2009 Renewable Energy Directive) which stablishes increasing use of renewable energy and overall reduction of energy consumption as a target for 2020. One of the polymers with greater diversity of applications and diversity of use is the Polypropylene. The material itself is difficult to degrade naturally so an incentive is necessary to recycle, recover and reuse it. Within this context, and with a growing social concern for environmentally sustainable solutions, there is the prospect of using plant fibers (typically abundant in tropical regions such as the Brazilian Northeast) in conjunction with this polymer to see if the mechanical and acoustic properties of the proposed composites are suited to those required by current safety and comfort standards. Once one possible combination of bamboo fibers and polypropylene meet the requirements of a particular application and after setting up a viable manufacturing method, it is possible to replace the materials used by the industry today by new less aggressive substances to the environment and, probably, lower indirect economic costs. Among the main results, the composite of recycled polypropylene with treated fibers and bi-directionally oriented presented a sound absorption coefficient up to 95% higher than the recycled polypropylene without any fibers.